The Conformational Coupling and Translocation Mechanism of Vitamin B(12) ATP-Binding Cassette Transporter BtuCD - Weng, Jingwei (The Biophysical Society, 2008)
ATP-binding cassette transporter BtuCD mediating vitamin B(12) uptake in Escherichia coli couples the energy of ATP hydrolysis to the translocation of vitamin B(12) across the membrane into the cell. Elastic normal mode analysis of BtuCD demonstrates that the simultaneous substrate trapping at periplasmic cavity and ATP binding at the ATP-binding cassette (BtuD) dimer proceeds readily along the lowest energy pathway. The transport power stroke is attributed to ATP-hydrolysis-induced opening of the nucleotide-binding domain dimer, which is coupled to conformational rearrangement of transmembrane domain (BtuC) helices leading to the closing at the periplasmic side and opening at the cytoplasmic gate. Simultaneous hydrolysis of two ATP is supported by the fact that antisymmetric movement of BtuD dimer implying alternating hydrolysis cannot induce effective conformational change of the translocation pathway. A plausible mechanism of translocation cycle is proposed in which the possible effect of the association of periplasmic binding protein BtuF to the transporter is also considered.